A study on the association of training volume of competitive collegiate male MLBB (Mobile Legends: Bang Bang) players to their diet quality as influenced by level of training distress - Calalang, Abigail Joy R.; Padua, Nigel T.; Tiongson, Kayla Arriadne S.; Callanta, Luz Felicidad S. (Quezon City College of Home Economics, University of the Philippines Diliman, 2023)
Esports players develop and improve their gaming skills by rigorously training for an average of 6-12 hours a day in a similar manner to their traditional physically athletic counterparts, including structured drills and competition scrimmages. Though it has been acknowledged that there is an association between nutrition and training distress in Esports players, there are not enough studies discussing the effect of competitive collegiate Esports training volume on their diet quality. This study aims to determine the association of training volume of competitive collegiate male MLBB (Mobile Legends: Bang Bang) players, and their diet quality as influenced by training distress. The participants of the study were composed of 80 competitive collegiate male MLBB Esports players from member schools and alliance organizations of the Collegiate Center for Esports (CCE) and AcadArena Philippines. The study used a quantitative descriptive-correlational research design to assess the association of training volume and diet quality among the participants as moderated by training distress. Training volume is assessed in terms of training time in both structured and unstructured training per week. Meanwhile, training distress is determined using the Training Distress Scale (TDS). Diet quality is assessed using the Diet Quality Index-International (DQI-I). Moreover, the study used descriptive statistics to describe the participants in terms of their sociodemographic profile, DQI-I score, training volume and TDS Score. Simple linear regression was used to determine the association of the training volume to the diet quality status and the association of the training to the diet quality status. Multiple linear regression was used to determine the moderating effect of training distress level to the association of training volume and diet quality. The results show that the respondents have an average total training time of 1772.85 minutes per week and a poor total DQI-I score (μ=44.79). There is a moderate amount of training distress (μ=22.14). Furthermore, there is no association between structured training volume and DQI components of the respondents. However, there is a low negative relationship with the unstructured training time and the total DQI-I score indicating that player’s personal decisions on training volume may inversely affect their diet quality. More so, there is no moderating relationship on the training distress to the association of training volume and diet quality. From a health perspective, this study emphasizes the need to take account the effect of Esports training to the nutritional status of the collegiate MLBB players.
Thesis
Bibliography: pages 88-101.
Keywords: Video gamers -- Philippines -- Nutrition; Video games -- Philippines